A least squares based meshfree technique for the numerical solution of the flow of viscoelastic fluids: A node enrichment strategy. (January 2015) - Lashkarbolok, Mohsen; Jabbari, Ebrahim; Westerweel, Jerry
Abstract: A fully implicit least-squares-based meshfree method is used to solve the governing equations of viscoelastic fluid flow. Here, pressure is connected to the continuity equation by an artificial compressibility technique. A radial point interpolation method is used to construct the meshfree shape functions. The method is used to solve two benchmark problems. Thanks to the flexibility of meshfree methods in domain discretization, a simple node enrichment strategy is used to discrete the problem domain more purposefully. It is shown that the introduced enrichment process have a positive effect on the accuracy of the results.